Micro-nano structure composite diffractive lens based on polymer nanocomposite, preparation process and wide-band high-efficiency imaging system thereof

CN122945188APending Publication Date: 2026-10-20INST OF OPTICS & ELECTRONICS CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611221071.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]本发明的目的在于针对现有技术存在的宽波段效率色散难以抑制、材料设计与结构设计脱钩、多层结构层间对准困难等问题,提供一种基于聚合物纳米复合材料的微纳结构复合衍射透镜及其制备工艺,通过“性能-材料-结构协同设计”实现宽波段高衍射效率

Benefits of technology

[0024](1)突破效率色散瓶颈:本发明通过“性能-材料-结构协同设计”方法,实现折射率差与波长成正比(Δn(λ)∝λ)的设计准则,提高了可见光波段(400-800 nm)平均衍射效率(≥90%),显著优于现有技术。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a micro / nano-structured composite diffractive lens based on polymer nanocomposite materials, its fabrication process, and a wide-band high-efficiency imaging system, belonging to the fields of micro / nano optics and diffractive optics. The micro / nano-structured composite diffractive lens based on polymer nanocomposite materials comprises a polymer nanocomposite mirror substrate layer and a double-layer composite structure. The double-layer composite structure includes a subwavelength micro / nano-diffractive structure layer and a filling layer. The subwavelength micro / nano-diffractive structure layer is disposed on the surface of the polymer nanocomposite mirror substrate layer, and the filling layer is disposed within the grooves of the subwavelength micro / nano-diffractive structure layer. This invention, through a "performance-material-structure co-design" method, achieves the design criterion that the refractive index difference is proportional to the wavelength (Δn(λ)∝λ), improving the average diffraction efficiency (≥90%) in the visible light band (400-800 nm), significantly outperforming existing technologies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of micro-nano optics and diffraction optics, and particularly relates to a micro-nano structure composite diffraction lens based on polymer nanocomposite materials, its fabrication process, and a wide-band high-efficiency imaging system. Background Technology

[0002] Micro- and nano-structured surfaces, as novel planar optical elements composed of subwavelength structural units, can flexibly control the phase, amplitude, polarization, and frequency of light waves, providing a revolutionary approach to achieving ultra-thin, lightweight, and on-chip integration of optical elements. Diffractive lenses based on micro- and nano-structured surfaces have shown great application potential in functional devices such as phase modulation, polarization manipulation, metasurface holography, and beam generation.

[0003] However, a core bottleneck exists in the practical application of micro / nano structure surface lenses for wide-band imaging: due to the wavelength sensitivity of micro / nano structure units, structural dispersion caused by propagation modes, unit structure resonance, and geometric phase is superimposed on the intrinsic dispersion of the material, resulting in a strong wavelength dependence of diffraction efficiency over a wide wavelength range—the "efficiency dispersion" problem. Existing solutions, such as utilizing multiple diffraction orders, optimizing microstructure parameters, reinforcing with high-refractive-index materials, and designing multilayer / hybrid structures, all optimize within a single dimension and cannot fundamentally break the strong wavelength dependence of diffraction efficiency. Furthermore, they face core challenges such as the decoupling of design and manufacturing processes, and limitations in materials and fabrication. Summary of the Invention

[0004] The purpose of this invention is to address the problems of wide-band efficiency dispersion that are difficult to suppress, material design and structural design are decoupled, and interlayer alignment of multilayer structures in existing technologies. It provides a micro-nano structure composite diffraction lens based on polymer nanocomposite materials and its fabrication process, which achieves high diffraction efficiency over a wide band through "performance-material-structure synergistic design".

[0005] A further technical problem to be solved by the present invention is to provide a wide-band high-efficiency imaging system including the above-mentioned micro-nano structure composite diffraction lens based on polymer nanocomposite materials.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A micro / nano-structured composite diffraction lens based on polymer nanocomposite materials includes a polymer nanocomposite mirror substrate material layer and a double-layer composite structure, wherein the double-layer composite structure includes a subwavelength micro / nano-diffraction structure layer and a filling layer.

[0008] The subwavelength micro / nano diffraction structure layer is disposed on the surface of the polymer nanocomposite mirror substrate layer, and the filling layer is disposed in the groove of the subwavelength micro / nano diffraction structure layer.

[0009] The material of the subwavelength micro-nano diffraction structure layer has a high refractive index and strong positive dispersion characteristics, while the material of the filling layer has a low refractive index and weak or negative dispersion characteristics. The materials of the subwavelength micro-nano diffraction structure layer and the filling layer satisfy the relationship that the refractive index difference is proportional to the wavelength: Δn(λ)∝λ.

[0010] The polymer nanocomposite mirror substrate layer comprises a polymer matrix and high-refractive-index inorganic nanoparticles; wherein the volume content of the polymer matrix is ​​70%-95%, and the volume content of the high-refractive-index inorganic nanoparticles is 5%-30%.

[0011] The polymer matrix is ​​polymethyl methacrylate, polycarbonate, polyimide or epoxy acrylate resin, and the high refractive index inorganic nanoparticles are rutile phase TiO2, ZrO2, ZnS, ITO or diamond, and the particle size of the high refractive index inorganic nanoparticles is <10 nm.

[0012] The surface of the high-refractive-index inorganic nanoparticles is modified with a silane coupling agent.

[0013] The fabrication process of the above-mentioned micro / nano-structured composite diffraction lens based on polymer nanocomposite materials includes the following steps:

[0014] S1: Preparation of polymer nanocomposite mirror substrate layer: First, the polymer nanocomposite mirror substrate layer is designed based on the Lorentz-Lorenz equation and effective medium theory, that is, the types and ratios of polymer matrix and high refractive index inorganic nanoparticles are determined; after surface modification, the high refractive index inorganic nanoparticles are uniformly dispersed in the polymer matrix, and polymer nanocomposite materials are prepared by solution blending or blending method; the polymer nanocomposite mirror substrate layer is prepared by spin coating or casting process.

[0015] S2: Preparation of subwavelength micro / nano diffraction structure layer: Based on scalar diffraction theory, analyze the relationship between efficiency dispersion and wavelength change to determine the optimal subwavelength micro / nano diffraction structure parameters; based on the subwavelength micro / nano diffraction structure parameters, process the subwavelength micro / nano diffraction structure on the surface of the polymer nanocomposite mirror base material layer prepared in step S1;

[0016] S3: Preparation of filling layer: Fill the grooves of the subwavelength micro / nano diffraction structure layer with filling layer material, and then perform heat treatment to obtain a micro / nano structure composite diffraction lens based on polymer nanocomposite material.

[0017] Specifically, in step S2, the subwavelength micro / nano diffraction structure is fabricated using microstructure contour lithography based on laser direct writing.

[0018] In step S2, the relationship between efficiency dispersion and wavelength variation is analyzed based on scalar diffraction theory to determine the optimal subwavelength micro / nano diffraction structure parameters. Specifically, genetic algorithm, particle swarm optimization algorithm or multi-objective Bayesian optimization algorithm is used, with material parameters and structural parameters as variables and process constraints as optimization constraints, with the goal of maximizing the average diffraction efficiency over a wide wavelength range. The process constraints include a minimum feature size ≥ 100 nm and an aspect ratio ≤ 5:1.

[0019] In step S3, vacuum spin coating is used for filling. The spin coating speed is 1000-3000 rpm, the spin coating time is 30-60 s, the vacuum degree is ≤10 Pa, the heat treatment temperature is 80-120℃, and the heat treatment time is 1-2 h.

[0020] The preparation process also includes the following steps:

[0021] S4: Functional verification: The fabricated micro / nano-structured composite diffraction lens based on polymer nanocomposite materials is integrated with the imaging system to construct a wide-band high-efficiency imaging system and perform functional verification.

[0022] A wideband high-efficiency imaging system comprising the aforementioned micro / nano-structured composite diffraction lens based on polymer nanocomposite materials.

[0023] The beneficial effects of this invention are as follows:

[0024] (1) Breaking through the efficiency dispersion bottleneck: This invention achieves the design principle that the refractive index difference is proportional to the wavelength (Δn(λ)∝λ) through the “performance-material-structure collaborative design” method, which improves the average diffraction efficiency (≥90%) in the visible light band (400-800 nm), which is significantly better than the existing technology.

[0025] (2) Solving the problem of design and process decoupling: This invention incorporates material parameters, structural parameters and process constraints into the same optimization framework to achieve integrated design of "material-structure-process", which fundamentally solves the dilemma of ideal design but difficult processing in traditional methods.

[0026] (3) Eliminate the interlayer alignment problem: The present invention adopts the integrated design of "double-layer shared micro-nano structure". The two layers of materials share the same micro-nano structure. Only single-layer high-precision processing is required to realize the equivalent double-layer optical function, avoiding the interlayer alignment problem in traditional multi-layer structures, and significantly reducing process complexity and alignment error.

[0027] (4) Achieving precise control of the optical properties of the lens base material: This invention achieves an equivalent refractive index control range of 1.4-1.8 (@550 nm) and material non-uniformity ≤ ±2% through polymer nanocomposite technology, providing a customizable lens base material basis for wide-band high-efficiency diffraction lenses.

[0028] (5) Lightweight advantage: The micro-nano structure composite diffraction lens based on polymer nanocomposite material prepared by this invention can achieve a weight reduction of ≥30%, which meets the requirements for lightweight optical load. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the micro / nano structure composite diffraction lens based on polymer nanocomposite materials according to the present invention.

[0030] Figure 2 This is a schematic diagram of the preparation process of the polymer nanocomposite mirror substrate material layer of the present invention;

[0031] Figure 3 This is a comparison of the wideband diffraction efficiency of the polymer nanocomposite-based micro / nano structure composite diffraction lens prepared in the embodiments of the present invention with that of a traditional micro / nano structure surface lens.

[0032] In the attached figures, the labels are as follows: 100 - polymer nanocomposite mirror substrate layer; 200 - subwavelength micro / nano diffraction structure layer; 300 - filling layer. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0034] A micro / nano-structured composite diffractive lens based on polymer nanocomposite materials includes a polymer nanocomposite mirror substrate material layer 100 and a double-layer composite structure. The double-layer composite structure includes a subwavelength micro / nano-diffractive structure layer 200 and a filling layer 300. The double-layer composite structure is used to modulate the phase of the incident light wave.

[0035] A subwavelength micro / nano diffraction structure layer 200 is disposed on the surface of the polymer nanocomposite mirror substrate material layer, and a filling layer 300 is disposed in the groove of the subwavelength micro / nano diffraction structure layer 200.

[0036] The subwavelength micro-nano diffraction structure layer 200 and the filling layer 300 share the micro-nano structure of the subwavelength micro-nano diffraction structure layer 200. Only a single layer of high-precision processing is required to achieve the equivalent double-layer optical function, which fundamentally avoids the interlayer alignment problem in multi-layer structures.

[0037] Preferably, the material of the subwavelength micro / nano diffraction structure layer 200 has a high refractive index and strong positive dispersion characteristics, and the material of the filling layer 300 has a low refractive index and weak or negative dispersion characteristics. The combination of the two materials satisfies the relationship that the refractive index difference is proportional to the wavelength: Δn(λ)∝λ, so as to achieve wavelength independence of phase delay in a wide band.

[0038] Preferably, the polymer nanocomposite mirror substrate layer 100 comprises a polymer matrix and high-refractive-index inorganic nanoparticles; the polymer matrix volume content is 70%-95%, and the high-refractive-index inorganic nanoparticle volume content is 5%-30%.

[0039] The polymer matrix is ​​polymethyl methacrylate, polycarbonate, polyimide or epoxy acrylate resin, and the high refractive index inorganic nanoparticles are rutile phase TiO2, ZrO2, ZnS, ITO or diamond. The particle size of the high refractive index inorganic nanoparticles is <10 nm to avoid Rayleigh scattering loss.

[0040] Preferably, the surface of the high-refractive-index inorganic nanoparticles is modified with a silane coupling agent to improve interfacial compatibility with the polymer matrix.

[0041] The fabrication process of the above-mentioned micro / nano-structured composite diffraction lens based on polymer nanocomposite materials includes the following steps:

[0042] S1: Preparation of polymer nanocomposite mirror substrate layer 100: First, the polymer nanocomposite mirror substrate layer 100 is designed based on the Lorentz-Lorenz equation and effective medium theory, that is, the ratio of polymer matrix and high refractive index inorganic nanoparticles is determined to achieve precise control of the target equivalent refractive index and dispersion characteristics; after surface modification, the high refractive index inorganic nanoparticles are uniformly dispersed in the polymer matrix, and polymer nanocomposite materials are prepared by solution blending or blending method; polymer nanocomposite mirror substrate thin film is prepared by spin coating or casting process, and the film thickness and uniformity are controlled.

[0043] S2: Preparation of subwavelength micro / nano diffraction structure layer 200: Based on the scalar diffraction theory, the relationship between efficiency dispersion and wavelength change is analyzed, and a multi-objective, multi-constraint collaborative optimization algorithm framework is established to determine the optimal subwavelength micro / nano diffraction structure parameters; based on the subwavelength micro / nano diffraction structure parameters, the subwavelength micro / nano diffraction structure is processed on the surface of the polymer nanocomposite mirror base material layer 100 prepared in step S1.

[0044] First, based on scalar diffraction theory, the relationship between the "efficiency dispersion" of surface diffraction elements in micro / nano structures and wavelength variation is analyzed, and a model is established to represent the relationship between diffraction efficiency η(λ) and phase delay Φmax(λ):

[0045] η(λ)=sin 2[1 / 2(Φmax(λ)-2π)] Formula (1);

[0046] Φmax(λ)=2πbΔn(λ) / λ Formula (2);

[0047] Where b is the physical height of the grating, and Δn(λ) is the refractive index difference between the two materials; based on the above formula, a multi-objective, multi-constraint collaborative optimization algorithm framework is established, taking both material parameters and structural parameters as variables, and process constraints as optimization constraints, with the goal of maximizing the average diffraction efficiency over a wide wavelength range, to determine the optimal micro / nano structure parameters. Then, based on the optimal micro / nano structure parameters, high-precision processing of subwavelength micro / nano diffraction structures is performed; specifically, microstructure contour lithography based on maskless laser direct writing, nanoimprint lithography, or diamond high-precision turning is used to process subwavelength micro / nano diffraction structures on the surface of the polymer nanocomposite mirror substrate material prepared in step S1.

[0048] S3: Preparation of Filling Layer 300: The filling layer material is filled into the grooves of the subwavelength micro / nano diffraction structure layer 200, and then heat-treated to obtain a micro / nano structured composite diffraction lens based on polymer nanocomposite materials. Specifically, on the surface of the subwavelength micro / nano diffraction structure processed in step S2, a second layer of polymer nanocomposite material with matching refractive index is filled by vacuum spin coating to form filling layer 300; the filled double-layer composite structure is heat-treated to eliminate interfacial stress and enhance interlayer bonding; performance characterization tests such as transmittance, diffraction efficiency, and transmission wavefront are performed, and the design and process parameters are iteratively optimized based on the test results.

[0049] Preferably, the laser-based direct-write microstructure contour lithography technology specifically includes: establishing a distortion pre-correction compensation model to pre-correct proximity effects, focusing errors, and astigmatism; performing secondary correction compensation through error analysis, establishing a nonlinear mapping model of light dose-development contour, and achieving pixel-level compensation. The process parameters of the laser-based direct-write microstructure contour lithography technology include: laser power and scanning speed. The optimal exposure dose distribution is obtained through multiple iterations to achieve high-precision control of subwavelength micro / nano structures.

[0050] Specifically, in step S2, the establishment of a multi-objective, multi-constraint collaborative optimization algorithm framework involves using a genetic algorithm, particle swarm optimization algorithm, or multi-objective Bayesian optimization algorithm. Material parameters and structural parameters are used as variables, and process constraints are used as optimization constraints. The goal is to maximize the average diffraction efficiency across a wide band. Process constraints include a minimum feature size ≥ 100 nm and an aspect ratio ≤ 5:1.

[0051] All calculations in this invention were performed using MATLAB (Matrix Laboratory) software.

[0052] Preferably, in step S3, vacuum spin coating is used for filling, with a spin coating speed of 1000-3000 rpm, a spin coating time of 30-60 s, a vacuum degree of ≤10 Pa, a heat treatment temperature of 80-120℃, and a heat treatment time of 1-2 h.

[0053] Preferably, the preparation process further includes the following steps:

[0054] S4: Functional verification: The fabricated micro / nano-structured composite diffraction lens based on polymer nanocomposite materials is integrated with the imaging system to construct a wide-band high-efficiency imaging system and perform functional verification.

[0055] Preferably, the high refractive index inorganic nanoparticles in step S1 are selected from rutile phase TiO2 (n≈2.7@550nm), ZrO2 (n≈2.2@550nm), ZnS (n≈2.4@550nm), ITO (n≈2.1@550nm), and diamond (n≈2.4@550nm), and the surface modifier is selected from silane coupling agent KH-570.

[0056] Preferably, the polymer material in step S1 is polymethyl methacrylate (PMMA, n≈1.49@550nm), polycarbonate (PC, n≈1.58@550nm), or polyimide (PI, n≈1.68@550nm), or epoxy acrylate resin (EA, n≈1.37@550nm).

[0057] Example 1

[0058] This embodiment provides a micro / nano-structured composite diffraction lens based on polymer nanocomposite materials, the structure of which is as follows: Figure 1 and Figure 2 As shown, it includes a polymer nanocomposite mirror substrate layer 100, a subwavelength micro / nano diffraction structure layer 200, and a filling layer 300.

[0059] Its preparation process includes the following steps:

[0060] S1: Design and fabrication of polymer nanocomposite mirror substrate layer 100. Polymethyl methacrylate (PMMA) was selected as the polymer matrix, and ZrO2 nanoparticles (5 nm in diameter) were used as high refractive index fillers.

[0061] (1) Based on the Lorentz-Lorenz equation and Maxwell-Garnett effective medium theory calculations in formula (3), it is determined that when the ZrO2 mass fraction is 21%, the equivalent refractive index of the composite material can reach 1.7@550 nm.

[0062] Formula (3);

[0063] Where n is the refractive index of the polymer matrix, ρ is the density of the polymer matrix, and N A R is Avogadro's constant, M is the molar molecular mass of the polymer matrix, α is the polarizability of the added nanoparticles, and R is the polarizability of the added nanoparticles. LL V0 is the molar refractive index of the added nanoparticles, and V0 is the volume of the nanoparticles in the polymer molecule.

[0064] (2) See Figure 2 ZrO2 nanoparticles were surface-modified with KH-570 silane coupling agent, then dissolved in toluene with PMMA. The mixture was ultrasonically dispersed for 2 h and magnetically stirred for 4 h to obtain a uniformly dispersed solution. A thin film was then prepared on a quartz substrate by spin coating at 2000 rpm for 60 s. The film was then heat-treated in a vacuum drying oven at 80℃ for 2 h to obtain a polymer nanocomposite mirror substrate layer 100 with a thickness of approximately 50 μm.

[0065] S2: Fabrication of subwavelength micro / nano diffraction structure layer 200.

[0066] (1) Theoretical design of subwavelength micro / nano diffraction structure. Based on scalar diffraction theory, a relationship model between diffraction efficiency and phase delay is established (Equation (1) and Equation (2)). With the visible light band of 400-800 nm as the target band, a diffraction lens with a focal length of f=100 mm and an aperture of D=50 mm is designed. Taking the process constraints (minimum feature size ≥100 nm, aspect ratio ≤5:1) as constraints, and with the goal of maximizing the average diffraction efficiency over a wide band, the optimal micro / nano structure parameters are determined as follows: grating height b=1.2 μm, period Λ=500 nm, and duty cycle 0.5.

[0067] (2) High-precision fabrication of subwavelength micro / nano diffraction structures based on laser direct writing. A German Heidelberg Instruments DWL 66+ laser direct writing system was used to fabricate subwavelength micro / nano diffraction structures on the surface of the polymer nanocomposite mirror substrate layer 100 prepared in S1. The fabrication parameters were: laser wavelength 405 nm, objective lens numerical aperture NA = 0.9, laser power 10 mW, and scanning speed 20 mm / s. Development was performed using a MIBK:IPA ratio of 1:3 developer for 60 s, followed by nitrogen drying.

[0068] S3: Preparation of Filler Layer 300: Construction of the Bilayer Composite Structure. On the surface of the subwavelength micro / nano diffraction structure processed in step S2, a second layer of material (low refractive index polymer, n≈1.4@550 nm) is filled by vacuum spin coating. The spin coating speed is 1500 rpm, the spin coating time is 45 s, and the vacuum degree is ≤5 Pa to ensure that the filler material completely fills the trenches of the micro / nano structure. Then, it is heat-treated in a vacuum drying oven at 100℃ for 1.5 h to eliminate interfacial stress.

[0069] S4: Functional verification: The fabricated micro / nano-structured composite diffraction lens based on polymer nanocomposite materials is integrated with the imaging system to construct a wide-band high-efficiency imaging system and perform functional verification.

[0070] Transmittance was measured using a spectrophotometer, and broadband diffraction efficiency was measured using a self-built diffraction efficiency testing system. The transmitted wavefront was measured using a Zygo interferometer. The test results show that the fabricated polymer nanocomposite-based micro / nano structured composite diffraction lens has an average diffraction efficiency of 96.1% in the 400-800 nm wavelength range, and the transmitted wavefront RMS ≤ λ / 15 (λ = 632.8 nm), meeting the design requirements.

[0071] Figure 3 This is a comparison of the broadband diffraction efficiency of the polymer nanocomposite-based micro / nanostructured composite diffraction lens prepared in this embodiment of the invention with that of a traditional micro / nanostructured surface lens. From... Figure 3 As can be seen, compared with traditional micro / nano structure surface lenses, the average diffraction efficiency of the polymer nanocomposite micro / nano structure composite diffraction lens prepared in this invention is ≥90% in the visible light band (400-800 nm).

[0072] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention. The above embodiments are provided only for the purpose of describing the present invention and are not intended to limit the present invention. Parts not described in detail in this specification are well-known in the art and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. All equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be covered within the scope of the present invention.

Claims

1. A micro / nano-structured composite diffraction lens based on polymer nanocomposite materials, characterized in that, The polymer nanocomposite material-based micro-nano structure composite diffraction lens includes a polymer nanocomposite mirror base material layer and a double-layer composite structure, wherein the double-layer composite structure includes a subwavelength micro-nano diffraction structure layer and a filling layer. The subwavelength micro / nano diffraction structure layer is disposed on the surface of the polymer nanocomposite mirror substrate layer, and the filling layer is disposed in the groove of the subwavelength micro / nano diffraction structure layer.

2. The micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to claim 1, characterized in that, The material of the subwavelength micro / nano diffraction structure layer has a high refractive index and strong positive dispersion characteristics, while the material of the filling layer has a low refractive index and weak or negative dispersion characteristics. The materials of the subwavelength micro / nano diffraction structure layer and the filling layer satisfy the relationship that the refractive index difference is proportional to the wavelength: Δn(λ)∝λ.

3. The micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to claim 1, characterized in that, The polymer nanocomposite mirror substrate layer comprises a polymer matrix and high-refractive-index inorganic nanoparticles; wherein the volume content of the polymer matrix is ​​70%-95%, and the volume content of the high-refractive-index inorganic nanoparticles is 5%-30%. The polymer matrix is ​​polymethyl methacrylate, polycarbonate, polyimide or epoxy acrylate resin, and the high refractive index inorganic nanoparticles are rutile phase TiO2, ZrO2, ZnS, ITO or diamond, and the particle size of the high refractive index inorganic nanoparticles is <10 nm.

4. The micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to claim 3, characterized in that, The surface of the high-refractive-index inorganic nanoparticles is modified with a silane coupling agent.

5. The fabrication process of the micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1: Preparation of polymer nanocomposite mirror substrate layer: First, the polymer nanocomposite mirror substrate layer is designed based on the Lorentz-Lorenz equation and effective medium theory, that is, the types and ratios of polymer matrix and high refractive index inorganic nanoparticles are determined; after surface modification, the high refractive index inorganic nanoparticles are uniformly dispersed in the polymer matrix, and polymer nanocomposite materials are prepared by solution blending or blending method; the polymer nanocomposite mirror substrate layer is prepared by spin coating or casting process. S2: Preparation of subwavelength micro / nano diffraction structure layer: Based on scalar diffraction theory, analyze the relationship between efficiency dispersion and wavelength change to determine the optimal subwavelength micro / nano diffraction structure parameters; based on the subwavelength micro / nano diffraction structure parameters, process the subwavelength micro / nano diffraction structure on the surface of the polymer nanocomposite mirror base material layer prepared in step S1; S3: Preparation of filling layer: Fill the grooves of the subwavelength micro / nano diffraction structure layer with filling layer material, and then perform heat treatment to obtain a micro / nano structure composite diffraction lens based on polymer nanocomposite material.

6. The fabrication process of the micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to claim 5, characterized in that, In step S2, the fabrication of subwavelength micro / nano diffraction structures specifically employs microstructure contour lithography based on laser direct writing.

7. The fabrication process of the micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to claim 5, characterized in that, In step S2, the relationship between efficiency dispersion and wavelength variation is analyzed based on scalar diffraction theory to determine the optimal subwavelength micro / nano diffraction structure parameters. Specifically, genetic algorithm, particle swarm optimization algorithm, or multi-objective Bayesian optimization algorithm is used, with material parameters and structural parameters as variables and process constraints as optimization constraints, with the goal of maximizing the average diffraction efficiency over a wide wavelength range. Process constraints include a minimum feature size ≥ 100 nm and an aspect ratio ≤ 5:

1.

8. The fabrication process of the micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to claim 5, characterized in that, In step S3, vacuum spin coating is used for filling. The spin coating speed is 1000-3000 rpm, the spin coating time is 30-60 s, the vacuum degree is ≤10 Pa, the heat treatment temperature is 80-120℃, and the heat treatment time is 1-2 h.

9. The fabrication process of the micro / nano-structured composite diffraction lens based on polymer nanocomposite materials according to any one of claims 5 to 8, characterized in that, The preparation process also includes the following steps: S4: Functional verification: The fabricated micro / nano-structured composite diffraction lens based on polymer nanocomposite materials is integrated with the imaging system to construct a wide-band high-efficiency imaging system and perform functional verification.

10. A wideband high-efficiency imaging system, characterized in that, The invention comprises the micro / nano structured composite diffraction lens based on polymer nanocomposite materials as described in any one of claims 1 to 4.